New record of Borniochrysa Brooks & Barnard, 1990 (Neuroptera: Chrysopidae) from China, with description of two new species - Wang, Maozhi; Lai, Yan; Liu, Xingyue (Zootaxa, 2022)
Borniochrysa Brooks & Barnard, 1990 (Neuroptera: Chrysopidae: Chrysopinae: Chrysopinae) is a green lacewing genus, with five species previously recorded from the Australian, Oriental, and Afrotropical regions. Here we report the first record of Borniochrysa from China, and describe two new species, Borniochrysa kamayaria sp. nov. and Borniochrysa zhenxiana sp. nov. The standard DNA barcoding region of cytochrome c oxidase subunit I (COI) of these two new species was sequenced. An identification key to the Borniochrysa species is also provided.